Controls on evolution of gas-hydrate system in the Krishna-Godavari basin, offshore India - Badesab, F.; Dewangan, P.; Usapkar, A.; Kocherla, M.; Peketi, A.; Mohite, K.; Sangode, S.J.; Deenadayalan, K. (2017)
In this study, we integrate environmental magnetic, sedimentological, and geochemical records of sediment core of Hole NGHP-01-10D overlying methane hydrate deposits to decipher the controls on the evolution of fracture-filled gas-hydrate system in the Krishna-Godavari (K-G) basin. Four distinct sedimentary units have been identified, based on the sediment magnetic signatures. An anomalous zone of enhanced magnetic susceptibility (Unit III: 51.9–160.4 mbsf) coinciding with the gas hydrate bearing intervals is due to the presence of magnetite-rich detrital minerals brought-in by the river systems as a result of higher sedimentation events in K-G basin and has no influence over hydrate formation. A strong to moderate correlation between magnetite concentration and chromium reducible sulfur (CRS) content indicates significant influence of sulfidization on the magnetic record and could be further exploited as a proxy to decipher paleo-H2S seepage events. Analysis of high-resolution seismic, bathymetry, and subbottom profiler data reveals the existence of a regional fault system in K-G basin. The opening and closing dynamics of the faults facilitated the migration and trapping of required gas concentrations resulting in accumulation of gas hydrates at the studied site. The seismic data provides support to the rock-magnetic interpretations. The observed variations in magnetic and geochemical properties have resulted from the episodic flow of methane and sulfide-enriched fluids through the fracture-filled network formed as a result of shale-tectonism. Our study demonstrated the potential of using an enviro-magnetic approach in combination with other proxies to constrain the evolution of gas-hydrate system in marine environments.